Improving image classification through descriptor combination - Mansano, A. [UNESP]; Matsuoka, J. A. [UNESP]; Afonso, L. C S [UNESP]; Papa, João Paulo [UNESP]; Faria, F.; Da, R. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The efficiency in image classification tasks can be improved using combined information provided by several sources, such as shape, color, and texture visual properties. Although many works proposed to combine different feature vectors, we model the descriptor combination as an optimization problem to be addressed by evolutionary-based techniques, which compute distances between samples that maximize their separability in the feature space. The robustness of the proposed technique is assessed by the Optimum-Path Forest classifier. Experiments showed that the proposed methodology can outperform individual information provided by single descriptors in well-known public datasets. © 2012 IEEE.
Keywords: Descriptor Combination; Evolutionary algorithms; Image classification; Combined informations; Data sets; Descriptors; Feature space; Feature vectors; Optimization problems; Optimum-path forests; Visual properties; Vector spaces